Pharmacological validation of Solanum mammosum L. as an anti-infective agent: Role of solamargine - Cabanillas, Billy; Chassagne, François; Vásquez Ocmín, Pedro; Tahrioui, Ali; Chevalier, Sylvie; Vansteelandt, Marieke; Triastuti, Asih; Amasifuen Guerra, Carlos Alberto; Fabre, Nicolas; Haddad, Mohamed (El Sevier, 2021)
Ethnopharmacological relevance: Fungal and bacterial infections remain a major problem worldwide, requiring the development of effective therapeutic strategies. Solanum mammosum L. (Solanaceae) (“teta de vaca”) is used in traditional medicine in Peru to treat fungal infections and respiratory disorders via topical application. However, the mechanism of action remains unknown, particularly in light of its chemical composition. Materials and methods: The antifungal activity of TDV was determined against Trichophyton mentagrophytes and Candida albicans using bioautography-TLC-HRMS to rapidly identify the active compounds. Then, the minimum inhibitory concentration (MIC) of the fruit crude extract and the active compound was determined to precisely evaluate the antifungal activity. Additionally, the effects of the most active compound on the formation of Pseudomonas aeruginosa biofilms and pyocyanin production were evaluated. Finally, a LC-HRMS profile and a molecular network of TDV extract were created to characterize the metabolites in the fruits' ethanolic extract. Results: Bioautography-TLC-HRMS followed by isolation and confirmation of the structure of the active compound by 1D and 2D NMR allowed the identification solamargine as the main compound responsible for the anti-Trichophyton mentagrophytes (MIC = 64 μg mL−1) and anti-Candida albicans (MIC = 64 μg mL−1) activities. In addition, solamargine led to a significant reduction of about 20% of the Pseudomonas aeruginosa biofilm formation. This effect was observed at a very low concentration (1.6 μg mL−1) and remained fairly consistent regardless of the concentration. In addition, solamargine reduced pyocyanin production by about 20% at concentrations of 12.5 and 50 μg mL−1. Furthermore, the LC-HRMS profiling of TDV allowed us to annotate seven known compounds that were analyzed through a molecular network. Conclusions: Solamargine has been shown to be the most active compound against T. mentoagrophytes and C. albicans in vitro. In addition, our data show that this compound affects significantly P. aeruginosa pyocyanin production and biofilm formation in our conditions. Altogether, these results might explain the traditional use of S. mammosum fruits to treat a variety of fungal infections and respiratory disorders.